PENGARUH TEBAL VENIR DAN BERAT LABUR PEREKAT TERHADAP KETEGUHAN REKAT KAYU LAPIS DAMAR - Adi Santoso (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
This paper present the study results on the effect of veneer thickness and glue spread on bonding strength of damar (Agathis spec.) plywood. The responses observed were the corrected absorption height measurement, depth of lathe check of veneers, veneers thickness, moisture content, specific gravity and plywood bonding strength. The design employed was tire randomized completely design with factorial experiment.The results showed that the effect of veneers thickness on plywood bonding strength was not significant, while the glue spread have significant effecton the plywood bonding strength. To meet damar plywood requirement for interior uses it ts advised to use 150 gm: perface of glue spread with urea formaldehyde adhesive.